1993
DOI: 10.1039/c39930001222
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of α-diazoketones derived fromL-amino acids and dipeptides using dimethyldioxirane. Synthesis and reactions of homochiral N-protected α-amino glyoxals

Abstract: Homochiral N-protected a-amino glyoxals are readily accessible by oxidation of a-diazoketones derived from natural amino acids and dipeptides using dimethyldioxirane in acetone; the glyoxals can be trapped efficiently in reactions such as Wittig olefination and condensation with amines and vicinal diamines.Without functional group protection amino glyoxals of type 1 would be expected to undergo spontaneous polymerisation. With appropriate N-protection they should be reasonably stable, yet amenable to a range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 6 publications
1
23
0
Order By: Relevance
“…Specific substrate-derived glyoxal inhibitors of proteases have been synthesized [31] and shown to be potent reversible inhibitors of chymotrypsin [32][33][34][35], subtilisin [36], papain [37], cathepsin B [35,38], cathepsin L [38], cathepsin S [39] and the proteasome [40]. In substrate-derived glyoxal inhibitors, the peptide carboxy group (RCOOH) is replaced by a glyoxal or keto-aldehyde group (RCOCHO) and the α-keto carbon of the glyoxal should occupy the same position as the hydrolysed peptide carbonyl of a peptide substrate.…”
Section: Substrate-derived Glyoxal Inhibitorsmentioning
confidence: 99%
“…Specific substrate-derived glyoxal inhibitors of proteases have been synthesized [31] and shown to be potent reversible inhibitors of chymotrypsin [32][33][34][35], subtilisin [36], papain [37], cathepsin B [35,38], cathepsin L [38], cathepsin S [39] and the proteasome [40]. In substrate-derived glyoxal inhibitors, the peptide carboxy group (RCOOH) is replaced by a glyoxal or keto-aldehyde group (RCOCHO) and the α-keto carbon of the glyoxal should occupy the same position as the hydrolysed peptide carbonyl of a peptide substrate.…”
Section: Substrate-derived Glyoxal Inhibitorsmentioning
confidence: 99%
“…Specific-substrate-derived glyoxal or α-keto-β-aldehyde (RCOCHO) inhibitors of proteases have been synthesized [1] and shown to be potent inhibitors of chymotrypsin [2][3][4], cathepsin B [3,5], cathepsin L [5], cathepsin S [6] and the proteasome [7]. We have recently [4] used "$C-NMR to study the mechanism of inhibition of chymotrypsin by specific-substrate-derived glyoxal inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Peptidyl diazoketones were treated with a solution of dimethyldioxirane in moist acetone (for preparation of ␣-keto-␤-aldehydes). It has previously been demonstrated that such an approach leads to formation of peptidyl ␣-keto-␤-aldehydes, in almost quantitative yield, by the oxidative cleavage of the diazo-group [13,17]. Compound identity was confirmed by mass spectral and elemental analysis in each instance.…”
Section: Resultsmentioning
confidence: 91%